Sky and night : a coming of age musical short film - Hoo, Priscilla Quee Lian (2011)
Sky & Night is a short film Directed by Phuong Dao and Produced by Priscilla Hoo, together with their key players; Aaron Ng (Director of Photography), Michelle Cheong (Production Designer), Philip Tan (Sound Supervisor) as well as Cheng Shian Wen (Post Supervisor), as their Final Year Project. The team is made up of final year students from the School of Art, Design and Media (ADM) in NTU. The duration of the entire film project took two semesters i.e 8 months, under the supervision of Prof Isaac Kerlow followed by Asst Prof Jaymz Wong.